The Interpersonal Legacy of a Positive Family Climate in Adolescence - Ackerman, Robert A. (2013)
This research evaluated how well overall levels of positive engagement in adolescents’ families of origin, as well as adolescents’ unique expressions of positive engagement in observed family interactions, statistically predicted marital outcomes approximately 20 years later. Data for family-of-origin positive engagement were drawn from approximately 400 families participating in the Iowa Youth and Families Project (IYFP) during three waves of data collection from 1989 to 1991. The primary outcomes were based on data from the IYFP in 2007 to 2008 and included marital behavior from 288 individuals and their spouses. Individuals’ unique family-of-origin expressions of positive engagement were linked to the degree of positive engagement they exhibited towards their spouses. A positive family climate during adolescence for one partner was also associated with marital outcomes for both partners. Overall, the results suggest that a positive climate in the family of origin may have long-term significance for subsequent interpersonal relationships.